Modified Sugiura Operation for Portal Hypertension and Bleeding Esophageal Varices - Khattab, Omar S.; Safar, Samie B. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: To find an operation that can be effectively carried out in both adults and children, equally applicable in the elective as well as in the emergency situation and for the good – risk as well as the poor – risk patients. Done by expert and junior surgeons in a short time. Patients and Methods: Twenty patients with portal hypertension and bleeding varices aged 9-45 years were treated with shunting procedures (group 1, n=10), or a modified Sugiura operation (group 2, n=10) in accordance with the following therapeutic protocol: after resuscitation and diagnostic endoscopy, an emergency modified Sugiura operation was carried out if bleeding could not be controlled over 24 hours. When bleeding could be controlled, the patients underwent full investigation and were then treated with either shunting procedure or with a modified Sugiura operation. The Fisher exact probability test was applied for statistical analysis.Results: Patients were evaluated at 1-3 years. The rates for operative deaths, recurrent hemorrhage, encephalopathy, late deaths, and patient survival at 1-3 years were as follows: 30%, 10%, 40%, 10% and 60% for group 1; 10%, 0%, 0%, 10%, and 80% for group 2, respectively. Within 3 months after the modified Sugiura operation, varices disappeared in most of the patients and hypersplenism was relieved in all.Conclusion: We conclude that the modified Sugiura operation is probably a reasonable treatment for variceal hemorrhage because it is effective in arresting hemorrhage and it’s recurrence, with no encephalopathy, and a good survival rate.